Bacterial diversity from environmental sample applied to bio-hydrogen production - Maintinguer, Sandra Imaculada [UNESP]; Sakamoto, Isabel K.; Adorno, M. Angela T.; Varesche, M. Bernadete A. (Elsevier B.V., 2015)
Environmental from tropical climate countries as sediments in standing waters are complex habitats which are able to provide favorable living conditions for manifold microbial species. The aim of this study was to evaluate the diversity of the anaerobic bacteria present in the sediment of the reservoir and its application in biological production of hydrogen gas. The anaerobic batch reactors showed a xylose consumption of 63.5% at 72 h of operation with yield of H-2 production of 0.3 (mol H-2/mol xylose) at 37 degrees C, pH 5.5. Molecular biology techniques used for genomic DNA extraction, cloning, sequencing and phylogenetic analyses of the sediment sampling revealed clones similar to the phyla Proteobacteria, Chloroflexi, Firmicutes, Deferribacteres, Fusobacteria, Cyanobacteria and uncultured bacteria, The analysis of DGGE revealed changes in microbial populations from the sediment and the anaerobic consortia of bacteria from the reactors fed with xylose. Anaerobic bacteria coming from the sediment, mainly rods forming endospores from Phylum Firmicutes were favored by the experimental conditions imposed and they were probably involved in the biologic process of the H-2 production. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Mesophilic conditions; Xylose; Sediment; 16S rRNA; DGGE